Grape leaf curl and protection against it in the vineyards of Zakarpattya of Ukraine - Fedorenko, V.; Yushchenko, L.; Lohoida, O.; Vachyla, G. (Quarantine and plant protection, 2022)
Goal. To clarify the features of biology, seasonal dynamics of flight, distribution, damage and protection of grapes from grape leafhopper Lobesia botrana Den. U Shift in Transcarpathia of Ukraine. Methods. Field. The research was conducted during 2018—2020 on the basis of Chizay LLC. The dynamics of the pest’s flight was studied by the method of pheromone monitoring using «Atrakon» pheromone traps and synthetic sex pheromones of the company «Csalomon» (Hungary). In order to detect damage to grapes by grape leafroller, the population of inflorescences by caterpillars of the first generation and bunches of the second generation was recorded. The records were made on two grape varieties — Merlot and Cabernet Sauvignon. In 2018—2020, Aktara 25 w.g. preparations were used against grape leaf curl in the vineyards under the conditions of Chizay LLC, Zakarpattia region. (thiamethoxam, 250 g/kg) and Mavrik EV (tau-fluvalinate, 240 g/l) according to generally accepted methods. Results. In connection with global warming, the phenology of the pest has changed somewhat. Based on this, the system of protective measures against cluster leaf curl must be adapted to today’s weather conditions. As a result of three-year observations, the changes that occurred in the flight dynamics of the grape leafhopper were recorded, in particular, the periods of mass reproduction of Lobesia botrana were determined depending on hydrothermal conditions, and the timing of protective measures was adjusted. Conclusions. The development and spread of cluster leaf curling was analyzed. In 2018 and 2019, the peak flight of the first generation of the cluster leafhopper was stable without sharp outbreaks of the spread of the pest — 155—161 copies/trap. In 2020, the development of the first generation of the leaf twister began sharply. During the mass flight period, 321 specimens/trap were recorded. In 2018, on the contrary, the second generation of leafhoppers developed rapidly — up to 313 butterflies per trap, this was facilitated by weather conditions. Such outbreaks of the number of grape leafhoppers led to significant damage to grapes and affected the yield. Damage to grapes at the initial stage of development and spread of the pest was: Merlot variety — 16—18%, Cabernet Sauvignon variety — 19—23%. In the control area, damage reached 30%. The effectiveness of chemical protection was 86.3—88.7%.